Deception in Negotiation: The Predicting Roles of Envy and Individual Differences - Cleoputri Yusainy; Ziadatul Hikmiah; Cathy Sofhieanty; Muhammad Ibrahim (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
Negotiations as a cooperative process naturally also contain competition, particularly towards negotiating partners who induce envy. Three components of envy i.e. (i) pain due to inferiority which either manifests in (ii) benign envy to improve the envier performance, or (iii) malicious envy that contains hostility and intention to hurt the envied, may motivate deceptive negotiation strategies. Regardless of the role of envy, individual differences in trait self-control and trait mindfulness may also predict deception. In this cloud-based online experiment, participants (N = 804 students) completed self-reported measures of trait self-control and mindfulness, read an envy scenario on their academics failure compared to the envied classmate, then randomly received the envy conditions (benign vs. malicious), filled in measure of state envy, read the negotiation scenario, and filled in measure of deception. We found that (i) at correlational level, deception was positively associated with all envy components but negatively associated with both individual differences, (ii) at prediction level, malicious and pain of envy predicted more deception, (iii) after taking into account the envy role, only trait self-control predicted lower level of deception. These findings may help improve ethical practices in negotiation context.